Growth, Productivity and Economics of Hybrid Rice as Influenced by Fertility Level and Plant Density - Mondal, S.; Bauri, A.; Pramanik, K.; Ghosh, M.; Malik, G. C.; Ghosh, D. C. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment conducted during kharif 2010 and 2011 at the Institute of Agriculture, Visva Bharati, Sriniketan, West Bengal, India showed that application of 125 kg N, 62.5 kg P2O5 and 62.5 kg K2O ha-1 (F3) improved the growth attributes (plant height, number of tillers m-2, leaf area index (LAI), dry matter accumulation, and crop growth rate) and increased yield components (number of panicles m-2, panicle length, number of spikelets panicle-1, number of grains panicle-1 and test weight) that led to high crop productivity of hybrid rice. Increase in plant density increased the plant height, tillers m-2, LAI, dry matter production and CGR. Panicles m-2 increased with increasing plant density; but all other yield components like panicle length, spikelets panicle-1, grains panicle-1 and test weight decreased with increasing plant density. Both grain and straw yield increased by increasing plant density. Crop at medium plant density (33 hills m-2) with 125 kg N, 62.5 kg P2O5 and 62.5 kg K2O ha-1 (F3P2) produced the highest grain yield (7039 kg ha-1) and paid the highest gross (` 87970 ha-1) and net returns (` 59695 ha-1). Higher growth attributes and greater yield components of hybrid rice at F3P2 combination led to high grain productivity (7039 kg ha-1). The study advocates growing of hybrid rice at a plant density of 33 hills m-2 (20×15 cm2 spacing) with 125 kg N, 62.5 kg P2O5 and 62.5 kg K2O ha-1 (F3P2) for its high productivity and profitability.